Investigating the UV-excess in Star Clusters with N-body Simulations: Predictions for Future CSST Observations*Supported by the research grants from the China Manned Space Project with No. CMS-CSST-2021-A08. (1st September 2022) - Pang, Xiaoying; Shu, Qi; Wang, Long; Kouwenhoven, M. B. N.
Abstract: We study the origin of the UV-excess in star clusters by performing N -body simulations of six clusters with N = 10 k and N = 100 k (single stars & binary systems) and metallicities of Z = 0.01, 0.001 and 0.0001, using petar . All models initially have a 50% primordial binary fraction. Using GalevNB we convert the simulated data into synthetic spectra and photometry for the China Space Station Telescope (CSST) and Hubble Space Telescope (HST). From the spectral energy distributions we identify three stellar populations that contribute to the UV-excess: (1) second asymptotic giant branch stars, which contribute to the UV flux at early times; (2) naked helium stars and (3) white dwarfs, which are long-term contributors to the FUV spectra. Binary stars consisting of a white dwarf and a main sequence star are cataclysmic variable (CV) candidates. The magnitude distribution of CV candidates is bimodal up to 2 Gyr. The bright CV population is particularly bright in FUV − NUV. The FUV − NUV color of our model clusters is 1–2 mag redder than the UV-excess globular clusters in M87 and in the Milky Way. This discrepancy may be induced by helium enrichment in observed clusters. Our simulations are based on simple stellar evolution; we do not include the effects of variations in helium and light elements or multiple stellar populations. A positive radial color gradient is present in CSST NUV − y for main sequence stars in all models with a color difference of 0.2–0.5 mag, up to 4 half-mass radii. The CSST NUV − g color correlates strongly with HST FUV − NUV for NUV − g > 1 mag, with the linear relation FUV − NUV =(1.09 ± 0.12) × (NUV − g ) + (−1.01 ± 0.22). This allows for conversion of future CSST NUV − g colors into HST FUV − NUV colors, which are sensitive to UV-excess features. We find that CSST will be able to detect UV-excess in Galactic/extragalactic star clusters with ages >200 Myr.